Let r be the radius of the circle.

The circle must have a center of (3 - r, 0).

So our formula is (x - 3 + r)^2 + y^2 = r^2

9(x - 3 + r)^2 + 9y^2 = 9r^2

x^2 /9 + y^2 /4 = 1

4x^2 + 9y^2 = 36

Subtracting the two formulas.

9(x - 3 + r)^2 - 4x^2 = 9r^2 - 36

5x^2 + (18r - 54)x + (117 - 54r) = 0

There is one solution when the discriminant is 0.

(18 - 54r)^2 - 4(5)(117 - 54r) = 0

r = 2(2 + sqrt(130))/27 (note that r can't be negative so it's not the other option)

Hope this was helpful.

=^._.^=